The Impact of Administrative Empowerment on the Level of Intellectual Capital: A Case Study of Saudi Arabian Airlines Company - Alkhurayyif, Saad; Al-Mutairi, Asma (The Arab Journal of Administration, 2022)
This study aimed to identify the effect of administrative empowerment on the intellectual capital of employees in the Saudi Arabian Airlines Company. To achieve the objectives of the study, a descriptive survey method was used by applying it to a convenience sample of company employees. The sample size was (257) employees. Among the most important findings of the study is the existence of a relatively acceptable degree for both administrative empowerment and intellectual capital at Saudi Arabian Airlines Company, and it was evident that there is a significant influence of administrative empowerment on the intellectual capital in Saudi Airlines Company, as the administrative empowerment recorded the highest impact on human capital, structural capital, and then relationship capital. Based on the results, the study concluded with a set of recommendations, the organization should take into consideration the correct activation of administrative empowerment by giving the employees power and an appropriate degree of independence, while activating methods of teamwork in performing tasks, and creating an appropriate organizational climate characterized by frankness, confidence, and knowledge sharing because the importance administrative empowerment to achieving intellectual capital and its role in achieving strategic goals. Finally, the researcher recommended the necessity of conducting more studies on intellectual capital in governmental and private organizations, as it is considered a source of distinction and achieves business continuity in the current knowledge economy era, and that requires full knowledge of it.